2006
DOI: 10.1007/s11255-006-9063-z
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthesia During Transrectal Ultrasonography-guided Prostate Biopsy: does it have any Effect on Sexual Function?

Abstract: Local infiltration with lidocaine does not seem to play a role in sexual dysfunction following prostate biopsies. Psychological factors influence patients and the urologist should be ready to inform and reassure both the patient and his family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Complications of the PPNB include pain due to puncture with the needle used for local anesthesia, symptoms associated with systemic lidocaine toxicity, urinary incontinence, degradation of the image resolution due to anesthetic injection, and increased vascularization within the periprostatic region 10. Stravodimos et al investigated the effect of PPNB during TRUS‐guided prostate biopsies on sexual behavior, and they concluded that local infiltration with lidocaine did not seem to play a role in sexual dysfunction following prostate biopsies 16. In our study group we encountered degradation of the image resolution in four patients (3.7%), but it had no influence on the biopsy procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Complications of the PPNB include pain due to puncture with the needle used for local anesthesia, symptoms associated with systemic lidocaine toxicity, urinary incontinence, degradation of the image resolution due to anesthetic injection, and increased vascularization within the periprostatic region 10. Stravodimos et al investigated the effect of PPNB during TRUS‐guided prostate biopsies on sexual behavior, and they concluded that local infiltration with lidocaine did not seem to play a role in sexual dysfunction following prostate biopsies 16. In our study group we encountered degradation of the image resolution in four patients (3.7%), but it had no influence on the biopsy procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of men on AS found that increased biopsy number correlated with decreased SHIM scores, but age, prostate volume, and prostate‐specific antigen (PSA) had no relation to decline in SHIM scores [12]. The psychologic interplay of AS and sexual function is highlighted by the finding that 6% of men experience some degree of SD in anticipation of a PB [13]. There is evidence that that men diagnosed with PCa after PB experience a greater decline in erectile function compared with men with benign biopsy results, indicating a potential psychologic effect of the cancer diagnosis on erectile function [14].…”
Section: Introductionmentioning
confidence: 99%